Pengembangan E-UKBM Dengan Aplikasi Kvisoft Flipbook Maker dalam Pembelajaran Fisika untuk Meningkatkan Kemampuan Problem Solving Peserta Didik - Gilang Pratiwi; Raden Wakhid Akhdinirwanto; Nurhidayati Nurhidayati (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2020)
The Self-Study Activity Unit Electronic (E-UKBM) is a small learning unit that orderly arranged from easy to difficult level based on e-learning using kvisoft flipbook maker application as the development of teaching material through interactive teaching media to improve students problem solving skill. E-UKBM has the characteristic of learning tool to achieve competency of knowledge and skill on teaching process using Sistem Kredit Semester (SKS). The aim of the use of E-UKBM is to improve students problem solving ability. This type of research develops the result of Plomp’s research design model, (1) Preliminary Investigation, (2) Design, (3) Realization/Contruction, (4) Tes, Evaluation, and Revision, (5) Implementation. The sample of this research is students of X MIA 3 SMA N 1 Purworejo. This data analysis was done by using the validity and reliability test, the problem solving ability test using the pre-test and post-test. The result of this study indicate that E-UKBM is valid, practical, and effective so that it is feasible to improve students problem solving ability.